2011
DOI: 10.1111/j.1574-695x.2011.00823.x
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ plays an essential role in the pathogenesis of gastric lymphoid follicles formation caused byHelicobacter suisinfection

Abstract: In this study, we aimed to assess the role of helper T cells in the development of gastric lymphoid follicles induced by Helicobacter suis infection. C57BL/6J mice were orally inoculated with H. suis. Six weeks after infection, gastric lymphoid follicles were observed in the gastric mucosa by hematoxylin and eosin staining, and the number of follicles was increased throughout the infection period. An immunohistological examination showed that the lymphoid follicles were composed of B cells, CD4-positive helper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 31 publications
3
18
2
Order By: Relevance
“…Further experimental infections of BALB/c and C57BL/6 mice using 9 H. suis strains, showed that all H. suis isolates induced a predominant T-helper (Th)17 response, but only mild upregulation of the Th2 cytokine interleukin (IL)-4, and no upregulation of Th1 markers, including interferon (IFN)-γ [98] . This contrasts with previously published data which showed that H. suis induced a predominantly Th1 local immune response, and IFN-γ had a major role in the gastric inflammatory process [99,102] . A possible explanation for these differences is that previous experimental infection studies have used homogenized gastric specimens from mice, pigs or non-human primates instead of pure bacterial isolates [99,102] .…”
Section: Infectionscontrasting
confidence: 56%
See 1 more Smart Citation
“…Further experimental infections of BALB/c and C57BL/6 mice using 9 H. suis strains, showed that all H. suis isolates induced a predominant T-helper (Th)17 response, but only mild upregulation of the Th2 cytokine interleukin (IL)-4, and no upregulation of Th1 markers, including interferon (IFN)-γ [98] . This contrasts with previously published data which showed that H. suis induced a predominantly Th1 local immune response, and IFN-γ had a major role in the gastric inflammatory process [99,102] . A possible explanation for these differences is that previous experimental infection studies have used homogenized gastric specimens from mice, pigs or non-human primates instead of pure bacterial isolates [99,102] .…”
Section: Infectionscontrasting
confidence: 56%
“…This contrasts with previously published data which showed that H. suis induced a predominantly Th1 local immune response, and IFN-γ had a major role in the gastric inflammatory process [99,102] . A possible explanation for these differences is that previous experimental infection studies have used homogenized gastric specimens from mice, pigs or non-human primates instead of pure bacterial isolates [99,102] .…”
Section: Infectionscontrasting
confidence: 56%
“…Several studies attribute a major role to IFN‐γ, mainly produced by B cells, in gastric lymphoid follicle formation in mice experimentally inoculated with stomach homogenate from H. suis ‐infected animals . This finding, again, partly contradicts the findings obtained when infecting mice with in vitro‐ isolated H. suis strains colonizing pigs …”
mentioning
confidence: 94%
“…Some studies have attempted to characterize the evoked immune response in the mouse, an animal species which has most often been used to model gastric Helicobacter infection. However, because of the fastidious nature of this micro-organism, these experimental infection studies were carried out using impure mucus or homogenized gastric tissue from infected mice, pigs or non-human primates, thus hampering interpretation of these results [18-20]. …”
Section: Introductionmentioning
confidence: 99%